SCADA systems in the industrial automation - Pérez-López, Esteban (2015)
This article focuses on the importance of monitoring systems, control and data acquisition, known as SCADA (for its acronym in English Supervisory Control And Data Acquisition), as a key aspect in the automation of manufacturing processes in the industry today. Technical and functional aspects of the implementation of SCADA systems are reflected, which enable humans interact with the processes in different industries without taking risks on the ground, allowing the control and decision making remotely from a control room. These systems or software, represent a huge impact on advancing industrial automation because, let graphically illustrate the production process on the display, create alarms and warnings in real-time and fully committed to the process to be controlled handling. Is mentioned the example of two industries that have implemented SCADA software, in order to provide improvements to their processes, achieving great results with the same.